2017
DOI: 10.1177/0047287517696980
|View full text |Cite
|
Sign up to set email alerts
|

Why Tourists Choose Airbnb: A Motivation-Based Segmentation Study

Abstract: Airbnb has grown very rapidly over the past several years, with millions of tourists having used the service. The purpose of this study was to investigate tourists’ motivations for using Airbnb and to segment them accordingly. The study involved an online survey completed in 2015 by more than 800 tourists who had stayed in Airbnb accommodation during the previous 12 months. Aggregate results indicated that respondents were most strongly attracted to Airbnb by its practical attributes, and somewhat less so by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
659
6
30

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(722 citation statements)
references
References 66 publications
27
659
6
30
Order By: Relevance
“…Researched aspects range from motivations of hosts and guests to use Airbnb (Guttentag, Smith, Potwarka, & Havitz, 2017;Ikkala & Lampinen, 2015;Stors & Kagermeier, 2015;Varma, Jukic, Pestek, Shultz, & Nestorov, 2016) and the economic impact for the wider community (Fang et al, 2016;Holm, 2016) to the spatial pattern of Airbnb in cities (Arias-Sans & Quaglieri, 2016;Cócola Gant, 2016;Gutiérrez et al, 2017). Airbnb's quick development can be placed within the context of postmodern tourism.…”
Section: Regulating the Impact Of Airbnbmentioning
confidence: 99%
See 1 more Smart Citation
“…Researched aspects range from motivations of hosts and guests to use Airbnb (Guttentag, Smith, Potwarka, & Havitz, 2017;Ikkala & Lampinen, 2015;Stors & Kagermeier, 2015;Varma, Jukic, Pestek, Shultz, & Nestorov, 2016) and the economic impact for the wider community (Fang et al, 2016;Holm, 2016) to the spatial pattern of Airbnb in cities (Arias-Sans & Quaglieri, 2016;Cócola Gant, 2016;Gutiérrez et al, 2017). Airbnb's quick development can be placed within the context of postmodern tourism.…”
Section: Regulating the Impact Of Airbnbmentioning
confidence: 99%
“…Next to these social factors, the lower prices (Guttentag, 2015;Gutiérrez et al, 2017;Stors & Kagermeier, 2015) are an important economic factor explaining the success of Airbnb (Oskam & Boswijk, 2016;Tussyadiah & Pesonen, 2016). Especially the growing number of commercial STRs, operating as traditional vacation apartments, seem to cater to tourists who are interested in finding a low-budget accommodation and not so much an authentic, local experience (for more information on different types of tourists and their motivations for using Airbnb, see Guttentag et al, 2017;Stors & Kagermeier, 2015).…”
Section: Regulating the Impact Of Airbnbmentioning
confidence: 99%
“…The spatial behaviour patterns of the hotel and P2P tourism offer are different [60]. This indicator illustrates the spatial prevalence of one over the other by calculating the subtraction of the intensities of both offers.…”
Section: Tourist P2p Prevalence Rate I Prmentioning
confidence: 99%
“…Also for existing users, potentials for cost saving are associated with consumer satisfaction (Möhlmann, ) and sharing intentions (Hawlitschek et al, 2016). Several studies identified financial benefits as one, if not the main reason for participation (Guttentag et al, ; Ozanne & Ballantine, ). In 2013, Forbes calculated the total of savings realized by consumers using sharing economy services to exceed $3.5 billion per year with a growth rate of 25% (Geron, ).…”
Section: Literature Reviewmentioning
confidence: 99%